Pengembangan Usaha Marble Cake pada Industri Rumah Tangga “Kari Cake Bali” di Banjar Jeleka, Batuan Sukawati Gianyar - I Wayan Gede Lamopia; Gusti Ayu Dessy Sugiharni (ADMA : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2022)
To maintain food security in Indonesia, it is necessary to participate in entrepreneurs engaged in food to continue to develop their businesses. The partner in this community service activity is Mrs. Ni Wayan Kariani who has a business called Kari Cake Bali with a business focus is making Marble Cake. Mrs. Kariani's business has been running for 11 years and is assisted by 3 employees. During a field visit to find existing partners, he said the last few years have experienced a decline in orders due to business competition. Specifically, Ms. Kariani said the competition was motivated by marketing limitations and the absence of innovation or development in her business. Based on these problems, the solution that has been given is product diversification activities and the digitalization of Kari Cake Bali.